Activation of PKA in cell requires higher concentration of cAMP than in vitro: implications for compartmentalization of cAMP signalling. Issue 1 (December 2017) - Koschinski, Andreas; Zaccolo, Manuela
Abstract cAMP is a ubiquitous second messenger responsible for the cellular effects of multiple hormones and neurotransmitters via activation of its main effector, protein kinase A (PKA). Multiple studies have shown that the basal concentration of cAMP in several cell types is about 1 μM. This value is well above the reported concentration of cAMP required to half-maximally activate PKA, which measures in the 100–300 nM range. Several hypotheses have been suggested to explain this apparent discrepancy including inaccurate measurements of intracellular free cAMP, inaccurate measurement of the apparent activation constant of PKA or shielding of PKA from bulk cytosolic cAMP via localization of the enzyme to microdomains with lower basal cAMP concentration. However, direct experimental evidence in support of any of these models is limited and a firm conclusion is missing. In this study we use multiple FRET-based reporters for the detection of cAMP and PKA activity in intact cells and we establish that the sensitivity of PKA to cAMP is almost twenty times lower when measuredin cell than when measuredin vitro . Our findings have important implications for the understanding of compartmentalized cAMP signalling.